'The little crystal eye would not blink': Jean Rouch and the camera eyewitness. (19th December 2018) - Fysh, William
Abstract: In a 1951 article series for Franc-Tireur, Jean Rouch described his fears as an ethnographic filmmaker. One must, he wrote, navigate between the detached observation of the 'dry-eyed savant' and the myopic immersion of a new 'Robinson Crusoe' bereft of his perspective-glass. If Rouch's anxiety touched on a familiar cliche of both ethnographic fieldwork and documentary filmmaking, it would nonetheless operate idiosyncratically in his work as a recurrent preoccupation with the possibilities of visual witnessing and the cooperation of human and camera eyes. In this essay I explore the genealogies of Jean Rouch's vision of témoignage, his experiments with the camera-as-witness, and the contribution of his filmmaking to a culture of visual witnessing on the cusp of what French historian Annette Wieviorka has called the 'era of the witness' in the 1960s. Focusing in particular on Moi, un noir/I, a Negro (1958) and Chronique d'un été/Chronicle of a Summer (1961), as well as Rouch's journalistic writings, television interviews and involvement with the Comité du film éthnographique in Paris, I argue that Rouch sought to develop a practice of visual witnessing in the service of a more humane cinema, one that might be adequate to the heterogeneity of its film participants. In developing such a practice, Rouch experimented with the camera's ability both to disclose and create the ambiguities and ambivalences of testimony – its simultaneously solitary and participatory voice, its extrovert interiority, its improvised repetition with difference of life 'as it was'.